2017
DOI: 10.3960/jslrt.17017
|View full text |Cite
|
Sign up to set email alerts
|

Optimum immunohistochemical procedures for analysis of macrophages in human and mouse formalin fixed paraffin-embedded tissue samples

Abstract: Macrophages are closely related to various diseases and it is therefore important that the properties of macrophages are adequately evaluated in human diseases and mouse disease models. Immunohistochemistry (IHC) of formalin fixed paraffinembedded (FFPE) samples is a very useful tool for examination of macrophages; however, an adequate IHC protocol is required for the examination of macrophage states. In this study, we assessed various antigen retrieval methods in order to devise the optimal protocols for stai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 30 publications
0
47
0
Order By: Relevance
“…We previously found that there was a significant correlation between PD‐L1 expression in cancer cells and macrophage infiltration in the tumor microenvironment, and macrophage‐derived tumor necrosis factor‐α was revealed to induce PD‐L1 overexpression via NF‐κB signal activation in pancreatic cancer . In the present study, macrophage infiltration was also detected by Iba‐1 IHC as described previously . Because it was difficult to count the macrophage density adequately in the sections, we could not evaluate the correlation between PD‐L1/2 TPS and macrophages.…”
Section: Discussionmentioning
confidence: 57%
“…We previously found that there was a significant correlation between PD‐L1 expression in cancer cells and macrophage infiltration in the tumor microenvironment, and macrophage‐derived tumor necrosis factor‐α was revealed to induce PD‐L1 overexpression via NF‐κB signal activation in pancreatic cancer . In the present study, macrophage infiltration was also detected by Iba‐1 IHC as described previously . Because it was difficult to count the macrophage density adequately in the sections, we could not evaluate the correlation between PD‐L1/2 TPS and macrophages.…”
Section: Discussionmentioning
confidence: 57%
“…Immunohistochemical analysis was performed essentially as described previously. 48 Antibodies used were as follows: anti-IL-34 (1D12; Abcam), anti-Iba-1 (#016-26461; Wako, Japan) and anti-CD163 (#10D6; Leica Biosystems, Nussloch, Germany).…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…TAM infiltration has been found to correlate with a poor prognosis in SCC . Of the several characteristic markers of macrophages, CD163 has been reported as a highly specialized marker of M2 monocyte‐derived alternative macrophages . Furthermore, CD163‐positive TAMs are chiefly associated with lymphatic vessel invasion and lymph node metastasis in OSCC via VEGF‐C expression …”
Section: Introductionmentioning
confidence: 99%